Economic and Environmental Assessment of Organic Lemon Cultivation: The Case of Southeastern Spain - Begoña García Castellanos; Benjamín García García; José García García (Agronomy, 2025)
Spain is the world’s leading producer of organic fresh lemons, with production concentrated in the southeast. Given the relevance of this region in lemon production and the role of organic agriculture in sustainable development, this study establishes the main organic lemon production models in Southeastern Spain (Fino and Verna) and evaluates them from the economic and environmental perspective using life cycle costing (LCC) and life cycle assessment (LCA). Both models present a similar cost structure, with labor and fertilization being the most significant costs. Verna presents higher unit cost due to lower productivity. Organic management entails higher unit costs than conventional due to lower productivity and the higher costs of organic fertilization and biotechnological pest control. In LCA, the contributions of the components to the impacts of the organic models are very similar, due to the similarities in the production models. These contributions also resemble those in conventional management systems, with fertilizers being the largest contributor to impacts. Organic systems generally show lower absolute values than conventional, mainly because of the use of organic fertilizers. Fino shows lower values than Verna, driven by higher productivity. The global warming results showed relatively low emissions, 0.053 and 0.068 kg CO2 eq·kg−1 for Fino and Verna, respectively. Additionally, a sensitivity analysis was performed, introducing variability in non-fresh marketable yields and considering the avoidance of synthetic fertilizers.